Pengembangan Kapasitas Aparatur Pemerintah Desa Di Desa Aek Korsik - Manalu, Mahdalena; Nasution, Husni Thamrin; Nasution, Irwan (Universitas Medan Area, 2018)
This research focuses on Capacity Building of Village Government Apparatus, Case Study of AekKorsik Village, AekKuo sub-district, the nature of this research is Descriptive. The ?results ?showed ?that? the ?ability ?of? the ?AekKorsik ?Village ?Government? Apparatus ?in AekKuo District, North LabuhanBatu District had not been maximized, thus impacting the overall performance of the Village Government Apparatus. In this study, researchers found that in the Capacity Development of AekKorsik Village Government Apparatus using the on the job method through internships and mentoring, and using the off the job method that is done by involving employees in the education and other education provided by the Government. And I hope that the training provided will be able to further improve the competence of village officials.?